Innovation of Population Administration Services with the “Done In The Hands” Application Salaman - Lestari, Annisa; Furwanti, Dina; Rahmawati, Risma; Santa, Rahmat; Ginanjar, Sunandie Eko (Institut Pemerintahan Dalam Negeri Kampus Sulawesi Selatan, 2024)
The Salaman application is one of the E-Government innovations created by Dispendukcapil which is a good innovation because it really makes it easier for the public to provide population administration services. The Salaman application provides birth certificates, identity cards (KTP), death certificates, population migration documents, child identity cards (KIA), family cards (KK), data correction, non-permanent resident registration. This research method uses a literature review with a qualitative approach, the data produced is in the form of words or descriptions. This research aims to determine the innovation of the Bandung City Dukcapil Office in creating the Salaman application and to determine the level of effectiveness of the Salaman application. The research results show that population administration services are running effectively, but in their implementation there are still several obstacles such as a lack of infrastructure and public knowledge of technology. The Bandung City Dukcapil Department can develop facilities and infrastructure and can socialize the Salaman Application Program to regional officials.